What Is the FDA Regulatory Framework for AI Medical Devices? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2020)
Artificial intelligence (AI) and machine learning (ML) are rapidly transforming the healthcare landscape, with medical devices being a key area of innovation...
Keywords: FDA Regulation and Compliance; Regulatory; Framework; Medical; Artificial Intelligence; Machine Learning; Healthcare